Development of e-Handout Based on Problem-Based Learning to Improve Students Cognitive on Rotation Dynamics - Safriana, Safriana; Gumanti, Vivi; Ginting, Fajrul Wahdi (Asian Journal of Science Education, 2023)
Learning outcomes in the 21st century require students to have the ability to think critically, carry out analysis, and find solutions. This research aims to determine the increase in students' cognitive learning outcomes after using e-handout-based PBL and to determine students' responses to e-handouts. This research method is the Research and Development (RD) uses the ADDIE model. This research is a nonequivalent control group design. The subjects in this research were expert validators, physics teachers, and 11th-grade students from State Senior High School 1 Syamtalira Aron. The research instruments use multiple choice test instruments, validation sheets, interview sheets, observation sheets and student questionnaires. Qualitative descriptive analysis technique is the data analysis technique used. The assessment results based on validation by e-handout-based PBL material experts obtained an average percentage for all aspects of 92.3% in the very good/decent category, e-handout-based PBL media experts obtained an average score of 90%. with the very appropriate category, and student responses obtained an average score of 89% in the "very good" category. The results of the experimental class analysis of the N-gain score were 71.02% in the "high" category. the control class obtained a score of 56.56% in the "medium" category. Based on data hypothesis testing using the Independent Sample t-test, the sig (2-tailed) value was 0.000. From the hypothesis it can be concluded that problem-based learning-based e-handouts are suitable for use and can improve students' cognitive learning outcomes.